In vitro and in vivo assessment of enamel colour stability in teeth treated with low-viscosity resin infiltration – a literature review - Polak-Kowalska, Karolina; Pels, Elżbieta (Journal of Stomatology, 2019)
Infiltration with a low-viscosity resin is one of the methods of minimally invasive treatment of enamel-induced hypo-mineralisation. It is one of the most modern methods of treatment of white lesions, which can be a bridge between remineralisation therapy and surgical methods. Long-term aesthetic effects of treatment depend on the colour stability of the resin used in this method. It is believed that due to the physical properties of the resin used in the infiltration method, there may be changes in the colour of the surface of the enamel subjected to infiltration. The paper attempts to summarise current reports regarding the colour stability assessment of enamel treated by infiltration with a low-viscosity resin confirmed in in vitro and in vivo studies. The previous results of laboratory tests indicate that the resin used in the infiltration method is susceptible to discolouration of internal and external origin. On the other hand, clinical trials prove that maintaining stable aesthetic effects of infiltration treatment is possible. It is assumed that the extent of discolouration may vary depending on the patient’s eating and hygiene habits. Therefore, prophylaxis has a strong impact on the quality of infiltrated surfaces. The aim of the work is to summarise current knowledge on the stability of the colour of the enamel surface treated by resin infiltration, based on a review of the selected literature. The analysis of the literature is also aimed at presenting the methods proposed by clinicians in the event of a change in the colour of the teeth subjected to the infiltration procedure.